A discrete choice experiment of the impact of consumers' environmental values, ethical concerns, and health consciousness on food choices: A cross-cultural analysis. Issue 4 (3rd April 2017) - Ghvanidze, Sophie; Velikova, Natalia; Dodd, Tim; Oldewage-Theron, Wilna
Abstract : Purpose: Over the last few decades, consumers' concerns for healthier lifestyles and the environment have become the driving forces for forming food-buying intentions. The purpose of this paper is to investigate the impact of product attributes regarding nutrition and health benefits of products, the environmental impact of production and social responsibility of producers on consumers' food and wine choices. Design/methodology/approach: The empirical analysis is based on an online survey conducted in the USA, the UK and Germany, and incorporates a discrete choice experiment with visual shelf simulations. Findings: Price and nutrition information are much more influential on consumers' food choices than information about social responsibility of producers or the ecological impact of production. Product attributes emphasizing the ecological impact of production and social responsibility of food producers are specifically valued by consumers with high levels of environmental consciousness and by those concerned about goods production. Consumers who are health conscious regarding their lifestyle and diets derive high utility values from the nutritional information of the product. Practical implications: The study contributes to an understanding of how to promote healthier food and wine choices and social and environmental responsibility of food and wine producers in various markets. Originality/value: The study offers a comparison of product attributes concerning ecological, social, nutrition and health benefits of the product; as well the investigation of congruent interrelationships between the consumers' values and related product attributes in three culturally distinct consumer groups.